Pre-colonial Eggon Warfare and the Humanization of War: Reflections on Just War Tradition - Alumbugu, Esson; Akut, Damian; O. Ogbaji, Julia (Journal of Central and Eastern European African Studies, 2026)
This paper examines the humanization of war among Eggon people of central Nigeria during the pre-colonial period from the perspective of the Just War tradition and the core principles under jus ad bellum and jus in bello. The paper argues that the humanitarian principles of war applied by Eggon people in pre-colonial times conformed to the principle of Just War. It uses primary and secondary sources to posit that the Just War tradition was not only universal but that some aspects of humanitarian principles underlying contemporary International Humanitarian Law were observed in pre-colonial Africa, including Eggonland. The paper concludes, therefore, that the existence of a Just War tradition among the Eggon people shows that contemporary IHL is not entirely foreign as some may suggest. As such African states should adhere more to IHL because it conforms to many of the humanitarian principles of war in pre-colonial Africa.